Persepsi Dan Harapan Mahasiswa Terhadap Ketersediaan E-Journal Di Perpustakaan Fakultas Peternakan Universitas Jambi - Maulana, Ade Novia; Yenti, Zarfina; Saputri, Barkah Dwi; Hidayah, Jam'ah Alfi (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
Intoduction. This research will discuss about students’ perceptions and expectations of the availability of e-journals in the animal husbandry faculty library Universitas Jambi. Data collection method. In this study will use a method that is quantitative. Data collection methods use are questionnaires, observation, interviews, and documentation. Analysis data. This is the questionnaire in the study will use a likert scale. The population in this study amounted to 265 students and the sample used was 73 respondents. In the sample technique, the research will use a random sampling technique or random sample. Result and discussion. Then the 8 indicators of perception, and the average result show that the score is in good category with each indicator’s score, namely acceptance (2,62), evaluation (2,73), ease of access(2,8), diversity of e-journals(2,15), utilization (2,56), access (2,96), cost (2,57), and recency (1,83). As for the results of the study will show that the score on the overall perception and also the expectations of students in the availability of e-journals in the animal husbandry faculty library Universitas Jambi is 20,22:8= 2,52 on the scale 2,51-3,27. Conclusions. So, it can concluded that the overall perceptions and expectations of students in the availability of e-journals in the animal husbandry faculty library Universitas Jambi are good.